The elusive quest for additionality. (May 2021) - Carter, Patrick; Van de Sijpe, Nicolas; Calel, Raphael
Highlights: Development finance institutions (DFIs) play a central role in mobilizing the private investment required to meet the Sustainable Development Goals. We demonstrate that a range of commonly used estimators suffer from systematic biases when applied to assess DFIs' effect on private investment. We discuss complementing quantitative with qualitative evidence, and propose a probabilistic approach to evaluating DFIs' investment additionality. Abstract: Development finance institutions (DFIs) annually invest $90 billion to support under-financed projects across the world. Although these government-backed institutions are often asked to show that their investments are "additional" to what private investors would have financed, it is rarely clear what evidence is needed to answer this request. This paper demonstrates, through a series of simulations, that the nature of DFIs' operations creates systematic biases in how a range of estimators assess additionality. Recognizing that rigorous quantitative evidence of additionality may continue to elude us, we discuss the value of qualitative evidence, and propose a probabilistic approach to evaluating additionality.